Research on the Letter to the Galatians: 2000-2020. Volume 1 - Tolmie, D. F. (UJ Press, 2023)
This book confirms that research on the Letter to the Galatians is flourishing. Although it is true that much of what is being published is not new and that well-known arguments and insights have often been repeated, it is also clear that much progress is constantly being made. In this volume, hundreds of academic studies that appeared on the letter from 2000 to 2020 are discussed concisely so that the main contribution of each study to a better understanding of the letter can be grasped easily. Studies on Galatians or parts of it are organised and discussed in terms of five categories – introductory matters, textual and stylistic issues, history of interpretation, interpretative approaches and the theology of the letter. The primary focus of each study is clearly delineated so that its specific contribution to grasping key aspects of the letter becomes clear. D. Francois Tolmie is Professor of New Testament Studies at the Faculty of Theology and Religion at the University of the Free State, Bloemfontein, South Africa. He is also the author of Persuading the Galatians: A Text-Centred Rhetorical Analysis of a Pauline Letter and Pointing Out Persuasion in Philemon: Fifty Readings of Paul’s Rhetoric from the Fourth to the Eighteenth Century